(3GdaQb Hjf GdXGA hGdVGOs - (3CHh GdbGSe SYO Hf Ydj Hf eMeO GdRfLGfis; (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, CHh GdYHGS, GdeYQha HGdeHQO,J (B286 (3g` s ((3GdEeGe eSYhO Hf SYjO Hf YHO Gddg GdehUdi s)
(3ChdgG (B:s
(3GNHQfG GdTjN YHO GddWja GdHZOGOi GdfMhi bGd gPG HGH eYQaI eG jcJH HGdVGO hGdXGA eYkG hGdaQb HjfgeG ai GdNW hGdgLGA s
(3BNQgG (B:s
(3hGdJbQjV HGdVGO GdTYQ hGdJbQjV GjVkG LQg GdHYjO EPG eVZgG Ke QOgG Edi Mdbg Je GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QhGjI GdbGV CHj GdaVd LYaQ Hf jMji Hf GHQGgje GdJejei Gdecis
(3cJH HNW ajg VHW s
(3YdjgG SeGY ddfGSN Ydi YHO GddWja Hf jhSa Hf eMeO GdHZOGOi HNW GdCNjQ faSg s
(3bQf GdfSN (B:s
Keywords: (3GddZIs